High Sensitivity Shortwave Infrared Photodetector Based on PbS QDs Using P3HT - Jin Beom Kwon; Maeum Han; Dong Geon Jung; Seong Ho Kong; Daewoong Jung (Nanomaterials, 2021)
Shortwave infrared (SWIR) photodetectors are being actively researched for their application in autonomous vehicles, biometric sensors, and night vision. However, most of the SWIR photodetectors that have been studied so far are produced by complex semiconductor fabrication processes and have low sensitivity at room temperature because of thermal noise. In addition, the low wavelength band of the SWIR photodetectors currently used has a detrimental effect on the human eye. To overcome these disadvantages, we propose a solution-processed PbS SWIR photodetector that can minimize harmful effects on the human eye. In this study, we synthesized PbS quantum dots (QDs) that have high absorbance peaked at 1410 nm and fabricated SWIR photodetectors with a conductive polymer, poly(3-hexylthiophene) (P3HT), using the synthesized PbS QDs. The characteristics of the synthesized PbS QDs and the current-voltage (I-V) characteristics of the fabricated PbS SWIR photodetectors were measured. It was found that the maximum responsivity of the optimized PbS SWIR photodetector with P3HT was 2.26 times that of the PbS SWIR photodetector without P3HT. Moreover, due to the high hole mobility and an appropriate highest occupied molecular orbital level of P3HT, the former showed a lower operating voltage.